Barth, Origen, and Universal Salvation: Restoring Particularity. By Tom Greggs - Widdicombe, Peter (The journal of theological studies, 2010)
As is immediately apparent from the title, this book, a revised Cambridge doctoral thesis, is something of a novelty. It is not often, if ever, that Origen and Barth have been brought into conjunction with each other in a sustained way for theologically constructive purposes. This Greggs readily acknowledges, but he maintains that such a comparison is not as odd as one might at first think.